Correlation Analysis between Nerve Fiber Layer Thickness and Peripapillary Vessel Density and Influencing Factors of Peripapillary Vessel Density in Preclinical Diabetic Retinopathy - Donghui Li; Qichang Wang (Journal of Ophthalmology)
Purpose. To observe the changes of the retinal nerve fiber layer (RNFL) thickness and the optic disc vessel density (VD) in preclinical diabetic retinopathy (DR) and the relationship between RNFL changes and VD, as well as to investigate the influencing factors on peripapillary vessel density. Methods. This was a cross-sectional study. Thirty-four eyes of 34 type 2 diabetes mellitus (T2DM) patients diagnosed with preclinical diabetic retinopathy (DR) were included in our study, with twenty-three eyes of 23 healthy subjects set up as normal controls. History of diabetes, hypertension, and dyslipidemia was recorded in detail. All participants underwent color fundus photography (CFP), RNFL around the optic disc, and OCT angiography (OCTA) over the optic disc. The 4.5 mm × 4.5 mm Angio Disc scan mode was performed with all participants by using the OCTA instrument. The relationship between changes of RNFL in the four quadrants (superior, inferior, temporal, and nasal) and VD changes was analyzed. Results. Vessel density was significantly lower in the superior (t = −2.27) and temporal (t = −2.02) peripapillary sectors of diabetic eyes compared to normal eyes (P<0.05). The retinal nerve fiber layer (RNFL) was significantly thinner in the temporal quadrant (P<0.001) of diabetic eyes compared to normal eyes. Pearson correlation coefficient analysis showed a significant positive correlation between vessel density and RNFL thickness in the peripapillary region in the temporal (r = 0.468, P<0.01) and superior (r = 0.612, P<0.01) sectors. Multiple linear regression analysis showed that glycated hemoglobin (HbA1c) (β = −1.50, P<0.01) and the duration of diabetes (β = −0.33, P=0.03) were associated with peripapillary vessel density. Conclusions. Preclinical DR presented optic disc microcirculation changes. Temporal RNFL thinning is an early sign of retinal neurodegeneration and is associated with temporal peripapillary vessel density reduction. The duration of diabetes and HbA1c are risk factors for peripapillary vessel density reduction in patients with preclinical DR.